Unveiling the potential of fine arts education in enhancing resilience among Chinese gifted students - Dong, Zhe; Zhang, Ying (Frontiers in Psychology, 2024)
Introduction The current study aimed to explore the complex dynamics influencing the resilience of gifted Chinese students, emphasizing the interconnected roles of fine arts education (FAE), creativity, and self-efficacy (SE). By examining the transformative potential of FAE, this research highlighted creativity and SE as key mediating factors for resilience among Chinese gifted students. Methods This study involves administering a structured set of questions to a sample of gifted young adults, thus achieving a high response rate of 93.21%. The Maus scale (1938) has been used to measure FAE, the Connor-Davidson Resilience scale assesses resilience, while creativity and SE are measured using the Kaufman scale and Schwarzer and Jerusalem scale, respectively. Statistical analyses includes a correlation matrix, ANOVA, confirmatory latent factor model tests, and mediation effect analysis for resilience and creativity. Data analysis has been conducted by using the SPSS Statistics 29.0, bootstrap, and AMOS 25.0 software. Results Current findings determines a significant role of FAE in enhancing emotional resilience, creativity, and SE among gifted students. This study also finds the importance of FAE in building essential coping mechanisms to address intellectual and emotional challenges specific to this group. Discussion This study proposes to integrate FAE into educational curricula to better support the intellectual and emotional needs of gifted young adults, thereby facilitating the development of coping skills crucial for their emotional wellbeing. Additionally, this study indicates the importance of art therapy and global initiatives in boosting the resilience, while preparing gifted students to face future challenges with enhanced psychological resilience.